CARA DAN TUJUAN PENCIPTAAN CANGKRIMAN WANCAHAN - P. Ari Subagyo (Sintesis, 2014)
This article discusses about cangkriman wancahan that is one of four kinds of cangkriman or Javanese traditional riddles. Javanese people created cangkriman wancahan in general by acronymization (acronym-making). The general way can be separated on two special ways, that are (1) acronimyzation in combining with shifting of presupposition and (2) acronymization in combining with foreign language spelling. The creating of the cangkriman wancahan is ended to (1) representing experiences, (2) laughing at situation, and (3) imitating foreign language spelling.Key words: cangkriman wancahan, Javanese, way, end, creating